Age and Kidney Disease Type as Key Determinants of Hemodialysis Utilization Among JKN Participants in West Java, Indonesia - Sita Nofitasari; Chatila Maharani (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Kidney disease remains a major contributor to the burden of noncommunicable diseases in Indonesia, and hemodialysis is the primary renal replacement therapy covered under the National Health Insurance (JKN). Understanding determinants of hemodialysis utilization is essential for improving service equity and effectiveness. The objective of this study was to identify determinants of hemodialysis utilization among JKN participants with kidney disease in West Java in 2022. This cross-sectional study analyzed secondary data from the BPJS Health Sample Data 2015–2022. A total of 310 respondents diagnosed with kidney disease (ICD‑10 N17–N19) and residing in West Java were included. Descriptive analysis, chi-square/Fisher’s exact tests, and logistic regression (backward LR) were performed to determine factors associated with hemodialysis utilization. Two variables were significantly associated with hemodialysis utilization: age and type of kidney disease. Productive-age participants had a lower risk of not receiving hemodialysis (OR = 0.329), indicating a protective effect. Participants of non‑productive age with acute kidney disease had the highest probability of not receiving hemodialysis (97.7%), whereas productive-age participants with chronic kidney disease had the lowest probability (35.8%). Age and type of kidney disease are key determinants of hemodialysis utilization among JKN participants in West Java. Productive-age individuals are more likely to receive hemodialysis, while non‑productive-age patients with acute kidney disease are at greatest risk of not receiving treatment.Keywords: hemodialysis; national health insurance; kidney disease; determinants; West Java, Indonesia